The Contestation of Maqasid al-Shari’ah Interpretation in Cassation Decision Number 386 K/AG/2024: Between the Istislahi Method and the Principle of Izalat al-Darar - Ilham Roozman; Muchlis Bahar; Elfia Elfia (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2026)
Marriage in Islam aims to realize sakinah, mawaddah, wa rahmah, but reality often shows the occurrence of domestic conflicts that lead to divorce. Religious Courts in Indonesia have the authority to resolve divorce cases based on positive law as well as the principle of maqasid al-shari'ah. This article aims to analyze comparatively the application of maqasid in three levels of divorce decisions, namely the Bukittinggi Religious Court (No. 509/Pdt.G/2023/PA. Bkt), Padang High Court of Religion (No. 71/Pdt.G/2023/PTA. Pdg), and the Supreme Court (No. 386 K/Ag/2024). This research uses a normative juridical method with a literature approach, sourced from court decisions, books, journals, and previous research, and analyzed through comparative methods. The results of the study show that the Religious Court and the High Court of Religion emphasize the principle of izālat al-dharar (removing harm) to protect the wife from repeated domestic quarrels, based on the principle of lā ḍarar wa lā ḍirār. On the contrary, the Supreme Court emphasized the istislah (public good) approach by rejecting divorce because the conflict is considered not to meet the requirements for broken marriage according to SEMA guidelines, as well as to maintain sharia goals in the form of hifz al-nasl and hifz al-usrah. This study concludes that there is a dialectic of maqasid interpretation in the practice of religious justice, which shows the methodological tension between the protection of the individual and the preservation of family institutions.